The Li isotope composition of marine biogenic carbonates: Patterns and mechanisms. (1st September 2018) - Dellinger, Mathieu; West, A. Joshua; Paris, Guillaume; Adkins, Jess F.; Pogge von Strandmann, Philip A.E.; Ullmann, Clemens V.; Eagle, Robert A.; Freitas, Pedro; Bagard, Marie-Laure; Ries, Justin B.; Corsetti, Frank A.; Perez-Huerta, Alberto; et al.
Abstract: Little is known about the fractionation of Li isotopes during formation of biogenic carbonates, which form the most promising geological archives of past seawater composition. Here we investigated the Li isotope composition (δ 7 Li) and Li/Ca ratios of organisms that are abundant in the Phanerozoic record: mollusks (mostly bivalves), echinoderms, and brachiopods. The measured samples include (i) modern calcite and aragonite shells from various species and natural environments (13 mollusk samples, 5 brachiopods and 3 echinoderms), and (ii) shells from mollusks grown under controlled conditions at various temperatures. When possible, the mollusk shell ultrastructure was micro-sampled in order to assess intra-shell heterogeneity. In this paper, we systematically characterize the influence of mineralogy, temperature, and biological processes on the δ 7 Li and Li/Ca of these shells and compare with published data for other taxa (foraminifera and corals). Aragonitic mollusks have the lowest δ 7 Li, ranging from +16 to +22‰, echinoderms have constant δ 7 Li of about +24‰, brachiopods have δ 7 Li of +25 to +28‰, and finally calcitic mollusks have the largest range and highest δ 7 Li values, ranging from +25‰ to +40‰. Measured brachiopods have similar δ 7 Li compared to inorganic calcite precipitated from seawater (δ 7 Li of +27 to +29‰), indicating minimum influence of vital effects, as also observed for other isotope systems and making them a potentially viable proxy of past seawater composition. Calcitic mollusks, on the contrary, are not a good archive for seawater paleo–δ 7 Li because many samples have significantly higher δ 7 Li values than inorganic calcite and display large inter-species variability, which suggests large vital effects. In addition, we observe very large intra-shell variability, in particular for mixed calcite-aragonite shells (over 20‰ variability), but also in mono-mineralic shells (up to 12‰ variability). Aragonitic bivalves have less variable δ 7 Li (7‰ variability) compared to calcitic mollusks, but with significantly lower δ 7 Li compared to inorganic aragonite, indicating the existence of vital effects. Bivalves grown at various temperatures show that temperature has only a minor influence on fractionation of Li isotopes during shell precipitation. Interestingly, we observe a strong correlation ( R 2 = 0.83) between the Li/Mg ratio in bivalve Mytilus edulis and temperature, with potential implications for paleo-temperature reconstructions. Finally, we observe a negative correlation between the δ 7 Li and both the Li/Ca and Mg/Ca ratio of calcite mollusks, which we relate to biomineralization processes. To explain this correlation, we propose preferential removal of 6 Li from the calcification site of calcite mollusks by physiological processes corresponding to the regulation of the amount of Mg in the calcifying medium. We calculate that up to 80% of the initial Li within the calcification site is removed by this process, leading to high δ 7 Li and low Li/Ca in some calcite mollusk specimens. Collectively, these results suggest that Mg (and thus [Li]) is strongly biologically controlled within the calcifying medium of calcite mollusks. Overall, the results of this study show that brachiopods are likely to be suitable targets for future work on the determination of paleo-seawater Li isotope composition—an emerging proxy for past weathering and hydrothermal processes.